Origins and Recent Development of Higher Level Apprenticeship in England : Paper prepared for the Seminar 'Berufliche Erstausbildung im Tertiärbereich - Modelle und ihre Relevanz aus internationaler Perspektive' Bonn 5 and 6 November 2012 - Steedman, Hilary [Verfasser] (My University, 2012)
The Higher Apprenticeship initiative in England builds on a valued and valuable tradition. Since at least the 1930s, some manufacturing companies in the UK were developing the technical knowledge base of their employees by funding them to study part-time in local Technical Colleges for a Higher National Certificate (HNC) qualification. These qualifications were recognised as a tertiary level qualification roughly equivalent to the first year or year and a half of a university degree level qualification and were and continue to be highly regarded in the engineering and technology sector. The HNC was specifically designed to be studied part-time by individuals already in employment in a relevant occupation. A matching qualification the Higher National Diploma (HND) was later introduced as a full-time equivalent to the HNC but never achieved the same level of employer recognition. In this paper, Section 1 will review skills policy in England from 1993 onwards with special reference to the development of apprenticeship under Conservative, Labour and Coalition governments. Section 2 will introduce the Higher Apprenticeship Initiative resulting from the Coalition's Skills Policy, and the reasons for its development, Section 3 will examine the structure of the qualification and give an example. Section 4 will conclude. (excerpt; BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 2.2.1 Westeuropa; Berufsbildungspolitik; Berufsbildung; Höhere Berufsbildung; Historische Entwicklung; England